Taming Heavier Group 14 Imine Analogues: Accessing Tin Nitrogen [Sn=N] Double Bonds and their Cycloaddition/Metathesis Chemistry. Issue 48 (25th October 2022) - Fischer, Malte; Roy, Matthew M. D.; Wales, Lewis. L.; Ellwanger, Mathias A.; McManus, Caitilin; Roper, Aisling F.; Heilmann, Andreas; Aldridge, Simon
Abstract: A systematic study to access stable stannaimines is reported, by combining different heteroleptic stannylenes with a range of organic azides. The reactions of terphenyl‐/hypersilyl‐substituted stannylenes yield the putative tin nitrogen double bond, but is directly followed by 1, 2‐silyl migration to give Sn II systems featuring bulky silylamido ligands. By contrast, the transition from a two σ donor ligand set to a mixed σ‐donor/π‐donor scaffold allows access to three new stannaimines which can be handled at room temperature. The reactivity profile of these Sn=N bonded species is crucially dependent on the substituent at the nitrogen atom. As such, the Sn=NMes (Mes=2, 4, 6‐Me3 C6 H2 ) system is capable of activating a broad range of substrates under ambient conditions via 1, 2‐addition reactions, [2+2] and [4+2] cycloaddition reactions. Most interestingly, very rare examples of main group multiple bond metathesis reactions are also found to be viable. Abstract : A systematic study on taming stannaimines (R2 Sn=NR) is reported by identifying a suitable supporting ligand framework for stannylenes in combination with organic azides. The nitrogen substituent of these compounds was crucial for allowing a broad range of subsequent reactivity ranging from cycloadditions to multiple bond metathesis reactions, thus highlighting the necessary balance of rendering challenging systems isolable but still reactive.